Whose wellbeing is it anyway? - Sunny Dhillon (Association for Learning Development in Higher Education (ALDinHE), 2018)
In this opinion piece, I suggest the need for a critical examination of the ‘wellbeing’ agenda currently being developed throughout Higher Education (HE) in the UK. I suggest that problems arise when notions of ‘wellbeing’ are used without being sufficiently well-defined, and are then accepted as the barometer of student health. This approach will be elucidated by contextualising the situation students find themselves in contemporary neoliberal universities; situating the crucial intermediary role that learning developers and student support services fulfil between academics and students; and exploring different modes of engagement available to those in these roles. Drawing upon the critical pedagogy of Biesta (2013), I argue that the remit of cultivating critical thinking and independent study skills means that learning developers, through one-to-one meetings, may sometimes be as well-placed as those with specific wellbeing roles (such as counsellors or mental health workers) to acknowledge and explore students’ personal and social anxieties and concerns with compassion. This approach may seem to be at odds with wellbeing rhetoric, which, I argue, can act to detract from critical engagement with the explicit challenges facing students in the contemporary socio-political milieu. My aim is therefore to reintroduce the notion of criticality within the discussions taking place among academics and professional support staff, which in turn may inform practice. Central to my aim in this is to raise broader questions around the primary role of academics and professionals in HE; for example, is it to train students to passively ‘fit in’ within society or to educate them in a manner such that they will act agentively in society?